Critical evaluation of ERP implementation on firm performance: a case study of AT&T. Issue 1 (30th May 2012) - Chan, Xin; Lau, Yui-yip; Ng, Jim Mi Jimmy
Firms have recently faced the twofold challenges of the abrupt deterioration of the global economy and continual rise in customer demands and expectations. Enterprise Resource Planning (ERP) benefits a firm in cost minimisation and service level enhancement. American Telephone and Telegraph Company (AT&T), the largest telecom service provider in the USA, is selected to be studied in this paper. We investigate the critical elements of their ERP implementation process. We also illustrate comprehensive approaches such as Cost-Benefit Analysis (CBA), Multiple Linear Regression and Intensity Indices to evaluate ERP performance. Findings show that ERP implementation decreases dependence on capital investment, but not for operating expenses. This study also found that AT&T reacted faster than the market average in terms of IT investment, and the Intensity Indices have shed some light on how this trend is derived.